Mentoring ELT pre-service teachers: To use or not to use L1 in language classroom - Ümit Özkanal; İlknur Yüksel (Journal of Pedagogical Research, 2023)
This study employed qualitative research methodology to investigate pre-service teachers' perceptions of L1 use in language classrooms and their reflections on mentor teachers' L1 use during practicum. In this way, the purpose of this study is to obtain a new perspective on the mentoring process of pre-service teachers during practicum, specifically in terms of L1 use as an important classroom dynamic in language teaching. 42 ELT pre-service teachers were selected and their teaching reflections and responses to open-ended questions were analyzed using a purposive sampling technique.  Initially, some pre-service teachers expressed a preference for minimal or no use of L1 to promote immersive L2 learning. However, their observations of mentors' successful use of L1 for classroom administration caused them to change their minds. The results emphasize the significance of pre-service teachers' reflections on mentors' use of L1 and their willingness to modify their beliefs and instructional strategies in response to observed effectiveness.